OPTIMALISASI PERKEMBANGAN ANAK MELALUI PENYULUHAN KESEHATAN TENTANG PENTINGNYA POLA ASUH CERDAS DAN STIMULASI PERKEMBANGAN ANAK BALITA DI PAUD MELATI, LILIBA, KOTA KUPANG - Jane Leo Mangi,; Agustina Ina,; Oklan BT Liunokas,; Dominggos Goncalves,; Yustinus Rindu, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Toddlerhood is a period of rapid growth and development and development. This period is a golden opportunity for child development that will not be repeated throughout human life. will not be repeated throughout human life. At this time it is very importantIt is very important that basic human needs are met, namely the needs of fostering, loving and nurturing. Attentionto the needs of asah or developmental stimulation as well as asih or smart parenting that supports child development is still not as vigorous as it should be. that supports child development is still not as vigorous as the attention to the needs of child growth. attention to the needs of child growth. Methods: This community service is carried out using the health counseling method. Implementation: Service This community service is carried out with the importance of smart parenting and child development stimulation at PAUD Melati, Liliba Village, Kupang City. Results: All mothers involved in this activity experienced an increase in knowledge about smart parenting and child development stimulation